Randomized Clinical Trial for Early Postoperative Complications of Ex-PRESS Implantation versus Trabeculectomy: Complications Postoperatively of Ex-PRESS versus Trabeculectomy Study (CPETS) - Arimura, S (2020)
10.1038/srep26080